PENERAPAN FLIPPED CLASSROOM BERBASIS PENDEKATAN MULTIREPRESENTASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA DIMASA PANDEMI COVID-19 - Ahmad Busyairi; Ni Nyoman Sri Putu Verawati; Hikmawati . (Karst : JURNAL PENDIDIKAN FISIKA DAN TERAPANNYA, 2022)
The purpose of this study was to determine the effectiveness of the application of Flipped Classroom based on a multi-representation approach in improving student understanding of concepts during the COVID-19 pandemic. The research method used a pre-experiment with a one-group pretest-posttest design. The sample consisted of 28 students of the Mathematics education study program at the University of Mataram class of 2021/2022 who were taking Basic Physics courses. The results of the study showed that the flipped classroom strategy based on a multi-representation approach could improve students' understanding of concepts in the high category (<g> = 0.71). It can be concluded that the flipped classroom strategy based on a multi-representation approach is effective in improving students' understanding of physics concepts, especially the concept of motion kinematics.